Zinc Niobate Hydrothermally Synthesized as a Catalyst for the Photodegradation of Organic Compounds - Nascimento, Josias do Rocio Vitor; Perek, Bruna; Matsushita, Alan Fernando Yoshiaki; Aguiar Leite, João Manoel de; Garcia, Jarem Raul (Orbital: The Electronic Journal of Chemistry, 2025)
Zinc Niobate ZnNb2O6 is a semiconductor compound that remains relatively unexplored for photocatalyst applications. In this work, we present a hydrothermal synthesis method that allows obtaining ZnNb2O6 with high surface area, nanometric size and high capacity for adsorption and degradation of dyes. Zinc niobate has a band gap of 3.36 eV and can be used as a photocatalyst when activated by ultra violet (UV) light, enabling the degradation of dyes and others organic compounds. Zinc niobate was tested as a photocatalyst for the degradation of methylene blue at different pH values and showed high dye degradation kinetics in both acidic and basic media.